PENGARUH MOTIVASI DAN KUALITAS TERHADAP KINERJA GURU DI SEKOLAH (Study kasus pada SMK Muhammadiyah 3 Singosari) - Ivar Nabilatul Akbar; Muhammad Mansur; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThis study aims to: a) know the partial influence Motivation (X1) and Quality (X2) on Performance (Y). B) to know and analyze simultaneously Motivation and Quality to the Performance of teachers in SMK Muhammadiyah 3 Singosari Malang. This research is a descriptive research with quantitative approach.Sources of data of this research is the distribution of questionnaires (questionnaires and questionnaires) to teachers at SMK Muhammadiyah 3 Singosari Malang. The data used is primary data. This analysis was performed using the SPSS program. The results of this study indicate that the variables of motivation and quality partially influence on the performance, while for the motivation variable has no partial influence on performance and for simultaneous test shows that the quality effect simultaneously on the performance.Keywords: Motivation, Quality and Performance